High-temperature CO2 Transcritical Heat Pump with Optimized Tube-in-tube Heat Exchanger - Huang Rui; Hu Bin; Trygve Magne Eikevik; Wang Ruzhu; Ge Tianshu (Zhileng xuebao)
In existing research, 90 °C is reported as the highest temperature of hot water supplied by a traditional CO2 heat pump. To supply pressurized hot water over 100 °C with the CO2 transcritical heat pump, a tube-in-tube heat exchanger was redesigned and optimized in this study. The internal heat exchanger system was adopted to verify the feasibility of a CO2 heat pump with an optimized tube-in-tube gas cooler to supply pressurized hot water over 100 °C. The influences of ambient temperature and inlet and outlet water temperatures on the heating capacity and system performance were studied by simulations and experiments. Results show that the error of experiment and simulation is less than 7.59%, 100 °C hot water can be obtained through the redesign of the gas cooler under high-temperature conditions. When the ambient temperature was 40 °C and the inlet water temperature was 9 °C, the highest COP (coefficient of performance) reached 3.64 in the experiment and 3.87 in the simulation. The highest COP in this study was 4.47 when the ambient temperature was 40 °C and the inlet and outlet water temperatures were 9 °C and 85 °C, respectively. With an increase in ambient temperature, the heating capacity increased and the COP exhibited the same variation trend as the heating capacity.